Terapi Inhalasi dengan Aromaterapi Lemon Menurunkan Tingkat Emesis Gravidarum Ibu Hamil Trimester I - Nasrawati, Nasrawati; Nurmawati, Nurmawati; Halijah, Halijah (Kisi Berkelanjutan: Sains Medis dan Kesehatan, 2025)
Nausea and vomiting (emesis gravidarum) are common complaints among pregnant women in their first trimester, which can disrupt nutritional balance and negatively impact maternal quality of life. Various non-pharmacological interventions, such as aromatherapy, have been employed to alleviate these symptoms. This study aims to examine the effect of lemon (Citrus limon) aromatherapy administered via inhalation on the severity of nausea and vomiting in first trimester pregnant women at the Wangi-Wangi Public Health Center. A quantitative research method was utilized, employing a pre-experimental design (one-group pretest-posttest). The study population consisted of 104 pregnant women, with a sample of 41 respondents selected through purposive sampling. Data were analyzed using the Wilcoxon signed-rank test. The results indicated that the mean score of nausea and vomiting prior to the intervention (pretest) was 16.05, while the mean score after the intervention (posttest) was 12.85. Statistical analysis revealed a p-value of 0.000 (p < 0.05), indicating a significant effect of lemon aromatherapy inhalation in reducing the severity of emesis gravidarum. In conclusion, lemon aromatherapy inhalation therapy is effective in alleviating nausea and vomiting in first trimester pregnant women. It is recommended that public health centers consider incorporating lemon aromatherapy as part of complementary midwifery care for managing emesis gravidarum.